“Mrs. So-and-so”: A love letter in the Indigenous Villages of the Pampas - Perna, Carlos Gabriel (2024)
Among the letters preserved in the archive of the indigenous Salinas Grandes settlement, a love letter was found. This letter had immediately a didactic, and mediately an exemplary function, like the others in the notebook that it was part of, which gives these letters an outstanding cultural value, since it deals not only with the mere use of writing, but also with the efforts of the indigenous society to ensure its preservation in the future. The love letter is an effect of the introduction of writing into the indigenous society and gives us access to profound transformation processes that were taking place within the Pampas and Patagonian societies at the time of the military conquest.